A healing curve: The poetry of Taqralik Partridge in Inuktitut translation - Henitiuk, Valerie; Mahieu, Marc-Antoine (Meta: Journal des traducteurs, 2022)
Curved against the hull of a peterhead (PS Guelph 2020), a slender volume of 19 poems that “wrestle with colonialism and racial violence while also reflecting a rich sensory imagery” (Partridge 2020a) was released in January 2020. By May of that year, this first book by prize-winning short-story writer, artist and spoken word poet Taqralik Partridge already figured in a list of “six Inuit literature greats” deemed essential reading. Although Partridge composed all of these poems in English, three translated versions are provided alongside their originals in curved against. The present article focuses on the two poems accompanied by Inuktitut versions, translated by Ida Saunders and Looee Arreak respectively, with a view to engaging with Partridge’s work from the perspective of eco-translation. The language related to nature – how it is employed and especially how it is translated – proves relevant to the discussion, as does the act of translation, which highlights the inter-relatedness critical to survival, literally and metaphorically speaking, for Inuit and non-Inuit alike. Curved against the hull of a peterhead (PS Guelph 2020), mince volume de dix-neuf poèmes qui « luttent contre le colonialisme et la violence raciale tout en laissant transparaître de riches images sensorielles » (Partridge 2020a), a paru en janvier 2020. Il s’agit du premier livre publié par Taqralik Partridge, autrice de nouvelles, artiste et poétesse reconnue. En mai de la même année, il figurait déjà sur une liste de « six grands titres de la littérature inuit » jugés comme des lectures essentielles. Bien que Partridge ait composé tous ses poèmes en anglais, trois de ceux contenus dans curved against s’accompagnent d’une version traduite. Le présent article se concentre sur les deux poèmes s’accompagnant d’une version traduite vers l’inuktitut, réalisée respectivement par Ida Saunders et Looee Arreak. Il s’agira d’en examiner les enjeux pour aborder l’oeuvre de Partridge dans la perspective de l’écotraduction. Le langage de la nature – ...